"They're Really Family!": Discursive Dynamics of Municipal Twinnings Between Louisiana and Acadian Communities of the Maritime Provinces. Issue 1 (1st December 2020) - Bruce, Clint
Abstract : Whether considered as a form of "diplomacy by cities, " as a strategy for small and mid-sized communities to assert their role amidst globalization, or as a means of territorial cooperation, twinnings between municipalities of different countries represent a common and oft celebrated facet of contemporary transnationalization. Sister cities in Louisiana and Canada's Maritime Provinces play an important part in the transnational networks among populations of the Acadian diaspora, a people "scattered to the wind" in the eighteenth century after mass deportation by British authorities. There are currently 12 such twinnings, and partnerships with the French-speaking world figure prominently in external subnational relations across the Maritimes, especially in New Brunswick. This article examines emerging discourses of diasporic Acadian identity through municipal twinnings between Louisiana and l'Acadie des Maritimes . After a general profile of twinnings in the Maritimes, I analyze the evolution of language used in sister-city agreements before offering examples of sister cities' unique contribution to a sense of diasporic belonging.